Mechanism of the initial oxidation of monounsaturated fatty acids. (30th October 2022) - Ding, Cong; Wang, Lu; Yao, YunPing; Li, Changmo
Highlights: Molecular orbital analysis indicated that H-atoms and peroxyl radicals set off β-fragmentation. Energy barriers and kinetic constants for allylic isomerization were presented. Allylic isomerization and β-fragmentation had a role in the different oxidation stages. Hydroperoxides contained more trans- than cis -structures. Abstract: The development of detection technology prompts the need to elaborate on the theory behind the oxidation of unsaturated fatty acids. This study integrates the detection of monounsaturated fatty acid oxidation at 60 °C with computational simulations to provide an advanced theoretical basis for the formation of hydroperoxides and allyl. The results indicate that oxidation reaction led to increases of 3.4 mg/g for 8-hydroperoxy- trans -9-octadecenoate ( trans8 ) and 2.7 mg/g for 9-hydroperoxy- trans -10-octadecenoate ( trans9 ) and 10-hydroperoxy- trans -8-octadecenoate ( trans10 ) despite low temperatures. The energy of peroxyl radical production was 0.36 kcal/mol and that of allylic isomerization was 78.52 kcal/mol, indicating the existence of two pathways for hydroperoxides formation: β-fragmentation and the allylic isomerization. Structural equation modeling (SEM) verified the multistep competitive side reactions that occurred during oxidation. This finding provides a new basis for future analysis of lipid oxidation.